2012
DOI: 10.1080/08927014.2012.710324
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically active biofilms: facts and fiction. A review

Abstract: This review examines the electrochemical techniques used to study extracellular electron transfer in the electrochemically active biofilms that are used in microbial fuel cells and other bioelectrochemical systems. Electrochemically active biofilms are defined as biofilms that exchange electrons with conductive surfaces: electrodes. Following the electrochemical conventions, and recognizing that electrodes can be considered reactants in these bioelectrochemical processes, biofilms that deliver electrons to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(109 citation statements)
references
References 186 publications
(202 reference statements)
2
95
0
4
Order By: Relevance
“…Electrochemically active biofilms have been investigated in microbial fuel cell research and researchers have tried to understand the mechanisms of electron transfer between microorganisms and metals (Babauta et al, 2012). Several molecular studies revealed the role of pili and of multiheme outer-membrane c-type cytochromes in electron transfer (Butler et al, 2010, Lovley, 2012.…”
Section: Perspectivesmentioning
confidence: 99%
“…Electrochemically active biofilms have been investigated in microbial fuel cell research and researchers have tried to understand the mechanisms of electron transfer between microorganisms and metals (Babauta et al, 2012). Several molecular studies revealed the role of pili and of multiheme outer-membrane c-type cytochromes in electron transfer (Butler et al, 2010, Lovley, 2012.…”
Section: Perspectivesmentioning
confidence: 99%
“…The poising of the anode was to allow consistent control of the biofilm electrode potential, by making the electrode as the sole electron acceptor [16]. The reason of nitrogen bubbling into the anode compartment was to accelerate the anaerobic condition in the system simultaneously increase the MFC electrochemical performance.…”
Section: Analytical Methods and Calculationmentioning
confidence: 99%
“…[6][7][8][9][10]. One key factor is accumulation of biomass on electrode surfaces [11][12][13][14][15][16], which could be reflected by geometrical status of bacterial biofilm formed on MFC anode electrodes. Biofilms, a synonym of microorganism communities attached to surfaces, are commonly formed and play a crucial role during various microberelated pathogenic, fermentative and energy-harvesting processes [12,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…One key factor is accumulation of biomass on electrode surfaces [11][12][13][14][15][16], which could be reflected by geometrical status of bacterial biofilm formed on MFC anode electrodes. Biofilms, a synonym of microorganism communities attached to surfaces, are commonly formed and play a crucial role during various microberelated pathogenic, fermentative and energy-harvesting processes [12,17,18]. Significant phenotypic changes happen during microbial transition from planktonic (freeswimming) to surface-attached forms, and biofilms often exhibit largely heterogeneous and complicated structures.…”
Section: Introductionmentioning
confidence: 99%